Integrating Value for the Consumer and Society: A New Conceptual Orientation for Strategic Marketing - Mazzarolo, Aloisio Henrique; Mainardes, Emerson Wagner; Azzari, Vitor (Wiley, 2026)
This study explores the evolving role of strategic marketing orientations in addressing contemporary societal challenges. While traditional orientations focus primarily on consumer needs or firm-centric objectives, emerging pressures for sustainability and social responsibility demand a broader conceptualization of value orientation. Drawing qualitative data from 32 interviews with managers, employees, consumers, and stakeholders, this research examines how marketing strategies can integrate individual and collective value propositions. The findings reveal key premises and mechanisms for aligning consumer interests with societal well-being, contributing to the theoretical discourse on value orientation. As a synthesis of these insights, we propose Consumer–Society Value Orientation (CSVO) as an emergent conceptual orientation that integrates consumer and societal value within marketing strategy. This study seeks to advance theory by positioning CSVO as a conceptual lens for future research on strategic marketing orientations that reconcile profitability with social impact.